Millennial 64 Vivienda para la ciudad de Ibagué - Castro Calderón, Daniela (Universidad Antonio Nariño, 2024)
The construction of housing today does not fully meet the housing needs of people and can also be largely responsible for the pollution of a city, which is why providing housing solutions that respond to the new dynamics and the demand for modern society is necessary so that the principles of sustainable development can be guaranteed and thus be able to generate a positive impact on the environment; Currently, the lack of housing spaces in the city of Ibague and the high costs of housing make it very difficult to acquire a home, although taking into account that in Colombia the rates of youth unemployment are higher every day and the levels of informality labor affect even more the achievement of housing, the development of a sustainable housing project is proposed in the city of Ibague that provides a solution to the aforementioned problems and responds to the needs of young adults from Ibague, in which the Co-living It will be the most profitable method to guarantee an optimal use of resources and space with the purpose of guaranteeing decent housing for young adults in the city of Ibague; This project is based on the construction of a building with around 200 living spaces, based on the system of collaborative spaces or Co-living that provide the maximum use of natural and economic resources and that is also based on the correct use of techniques of environmentally friendly construction, Millennial 64 as the housing project is called, seeks to generate decent housing spaces for young adults in the city of Ibague while caring for the environment and natural resources is guaranteed.